Does international trade promote economic growth? Europe, 19th and 20th centuries - Oscar Bajo-Rubio; María del Carmen Ramos-Herrera (Global Labor Organization (GLO), 2023)
In this paper, we analyse the relationship between international trade and economic growth in an unbalanced panel of 20 European countries in a long-term perspective, since the mid-19th century to present days, differentiating between the periods before and after the start of the Second World War. To this end, we perform Granger-causality tests between exports and GDP, and between imports and GDP, following the novel methodology of Juodis et al. (2021) for panel data models with large cross-sectional and time series dimensions. Our results support the existence of a bi-directional relationship between both trade variables and GDP, for the whole period and across subperiods.
Keywords: F41; F43; N10; O47; 330; International trade; Economic growth; Europe; Granger-causality